A rapid turnaround gene panel for severe autoinflammation: Genetic results within 48 hours - McCreary, Dara; Omoyinmi, Ebun; Hong, Ying; Jensen, Barbara; Burleigh, Alice; Price-Kuehne, Fiona; Gilmour, Kimberly; Eleftheriou, Despina; Brogan, Paul (Frontiers in Immunology, 2022)
There is an important unmet clinical need for fast turnaround next generation sequencing (NGS) to aid genetic diagnosis of patients with acute and sometimes catastrophic inflammatory presentations. This is imperative for patients who require precise and targeted treatment to prevent irreparable organ damage or even death. Acute and severe hyper- inflammation may be caused by primary immunodeficiency (PID) with immune dysregulation, or more typical autoinflammatory diseases in the absence of obvious immunodeficiency. Infectious triggers may be present in either immunodeficiency or autoinflammation. We compiled a list of 25 genes causing monogenetic immunological diseases that are notorious for their acute first presentation with fulminant inflammation and which may be amenable to specific treatment, including hemophagocytic lymphohistiocytosis (HLH); and autoinflammatory diseases that can present with early-onset stroke or other irreversible neurological inflammatory complications. We designed and validated a pipeline that enabled return of clinically actionable results in hours rather than weeks: the Rapid Autoinflammation Panel (RAP). We demonstrated accuracy of this new pipeline, with 100% sensitivity and 100% specificity. Return of results to clinicians was achieved within 48-hours from receiving the patient’s blood or saliva sample. This approach demonstrates the potential significant diagnostic impact of NGS in acute medicine to facilitate precision medicine and save "life or limb" in these critical situations.